2009
DOI: 10.1111/j.1365-2265.2009.03555.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders in acromegaly: a cross‐sectional study in 81 acromegalic patients

Abstract: Acromegaly is associated with an increased prevalence and a specific pattern of affective disorders. Greater emphasis on diagnosing and treatment of mental disorders in acromegalic patients might improve the disease management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 35 publications
1
62
1
4
Order By: Relevance
“…The emotional and psychological effects of such lingering changes have so far not been thoroughly studied. Previous studies have reported an increased risk of psychopathology and maladaptive personality traits in patients with active acromegaly and those who have been in long-term remission (8,21,22). However, to date there has been no satisfactory explanation of this phenomenon except that it may be related to irreversible changes associated with previous GH excess (8).…”
Section: Discussionmentioning
confidence: 77%
“…The emotional and psychological effects of such lingering changes have so far not been thoroughly studied. Previous studies have reported an increased risk of psychopathology and maladaptive personality traits in patients with active acromegaly and those who have been in long-term remission (8,21,22). However, to date there has been no satisfactory explanation of this phenomenon except that it may be related to irreversible changes associated with previous GH excess (8).…”
Section: Discussionmentioning
confidence: 77%
“…Patients with CD are frequently affected by major psychiatric disorders such as depression, anxiety and psychosis, even after long-term biochemical cure of the disease (8,9). Besides, there is an increased prevalence of affective disorders or anxiety-associated personality traits in patients with acromegaly and prolactinomas (10,11). Interestingly, patients with NFPA exhibited a comparable personality pattern, potentially as a result of the pituitary lesion and/or associated hormonal dysregulations (12).…”
Section: Introductionmentioning
confidence: 99%
“…19 Long-standing exposure to IGF-1 and GH interferes with the regulation of trophic processes in many organ systems and is supposed to affect brain function and structures. 6 Several findings suggest that the GH has an important role during brain development.…”
Section: Discussionmentioning
confidence: 99%
“…5 In the literature, there is a limited study about structural and metabolic changes in the brains of patients with acromegaly. [5][6][7][8][9] Diffusionweighted imaging and diffusion tensor imaging (DTI) techniques provide microstructural information about biological tissue damage that cannot be obtained with other imaging modalities. 10 DTI has already improved the scientific understanding of many neurologic and psychiatric disorders.…”
mentioning
confidence: 99%